WORKABILITY CONDITIONS DETERMINATION OF NETWORK DISTRIBUTION WITH OVERHEAD LINES POWER TRANSMISSION WITH THE 6-35 KV - KUTIN, VASYL; KUTINA, MARINA; KOVALOV, ARTEM (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The principal of identification of isolation workability in relation to a ground was proposed. It is based on the electrosafety criteria usage and a minimum current flow to a ground. The conditions of workability of isolation of distribution network is calculated in look of changes of isolation workability restrictions in relation to regulations and standards. The Method of parameters of isolation phase calculation was developed in relation to a ground by continuous of common active isolation resistance and voltage phase in relation to a ground and results analysis with the help of special diagnostic model which shows the dependence of parameters of isolation from controllable items. For the calculation of data work and determination of isolation workability DN in relation to a ground was made a structure and algorithms of diagnostic complex functioning that contains the subsistence of constant and periodic control and algorithmical program software oh the base of microcontroller. The main cause of insulation damage is the formation of shunt connections between the conductive part and the ground in electrical distribution networks with a voltage of 6-10 kV. In this case, there are two processes - a smooth symmetrical decrease in the active resistance of the insulation phases due to the action of moisture on the surface of the insulators and an asymmetric sharp decrease in the active resistance of the insulation of individual phases relative to the ground due to shunt connections. Determining the conditions of insulation performance of the distribution network in the form of restrictions on changes in insulation performance in relation to the ground, in accordance with regulations and standards, it is necessary to limit the amount of current through shunting minimum electricity losses.
Keywords: distribution network; isolation control; workability conditions determination; diagnostical complex